Descriptive analysis of the results of the state of Paraíba in the National Assessments of Patient Safety Practices 2016-2019 (Research, Society and Development, 2022)
This study aims to present the results of the indicators evaluated in the state of Paraíba in the National Assessments of Patient Safety Practices 2016-2019. A quantitative and qualitative, descriptive and retrospective study was carried out on the reports released from 2017 to 2020 by Anvisa that show the results of the health services in Paraíba that participated in the Assessments. As a result, the year with the highest and lowest proportion of participating services was identified, as well as the number of non-conformities, the criteria with the best and worst results and the list of health services classified as high adherence over the years. We conclude that it is not possible to compare the results due to the variability of the participating services, as well as the inclusion of new evaluation criteria over the years and changes in the codification of the analyzed criteria, however with an annual and punctual analysis of the information contained in the published reports, measurements can be made, including knowing the indicators that need to be improved in compliance and guiding decision-making for the implementation and/or implementation of strategies to raise the quality of care through the Patient Safety practices of the services participating in the evaluation in the territory of Paraíba.